INTERTEXTUAL ELEMENTS, THEIR FUNCTIONS IN THE TEXT (BASED ON THE NOVEL "KYS" BY T. TOLSTOY) - Dilbar Jabborova; Xazipova Zulfiya (Social science and innovation, 2023)
The study showed that the text of literary works becomes intertextual. Currently, there is growing interest in studying the problems of incorporating elements into a text using high artistic methods, depending on the level of intertextual theory that dominates in the fields of linguoculturology and literary criticism. In this regard, the article analyzes intertextual elements and their functions in Tolstoy’s novel “Kys